Abdominal Tuberculosis in Yemen - AL-SARRAF, Salem A.H. (Journal of the Faculty of Medicine Baghdad, 2008)
Background:tuberculosis is an endemic disease in Yemen. Abdominal Tuberculosis (AT) is the most common extra pulmonary manifestation of the disease.The clinical picturecan be non specific.Laparoscopy is the most accurate diagnostic method but has its limitation depending on presentation.The aim of this study was to present the common clinical manifestation and the different type of Abdominal TB,the surgical procedure used,the morbidity andmortality of the disease. Patient and Methods:This is a prospective study of 48 patients with Abdominal TB who were admitted to Kuwait University hospital in Sana'a-Yemen between Jan 2002-Dec2004.fourteen patients (29%) were treated medically with Anti TB drugs.Thirty four patients (71%) required surgical Intervention for diagnosis and treatment.Results :Thirty two patients (67%) were female ,16 patients ( 33%) were male with a ratio of 2:1 .Fifty percent of patients were in age group 20-40.The most commonsymptom was Anorexia (94%) abdominal pain (92%) fever (90%).The most common signs were Abdominal mass ,ascitis and abdominal tenderness.Smearesand culture of ascitis fluid were negative for A.F.B. Out of the 34 patients who required surgical treatment ;17 patients (50%) had Tuberculous peritonitis,32% had tuberculosis of intestine, and 17%had tubeculous mesenteric lymphadenitis.Complication rate was 50%,and mortality was 9%.Conclusions:Diagnosis of Abdominal TB should be suspected in patients of abdominal pain with vague clinical presentation coming from endemic areas.not all patients presentwith ascitis and whene ascitis is present smears and culture are usually negative for A.F.B. Laparoscopy has its limitation Surgery should be avoided unless complicationoccur and should be conservative.Tube drains can be used with no fear of TB Sinus.